Synthesis, structure and luminescent properties of a new blue-green-emitting garnet phosphor Ca2LuScZrAl2GeO12:Ce3+. Issue 73 (20th July 2016) - Zheng, Yaling; Zhuang, Weidong; Xing, Xianran; Zhong, Jiyou; Liu, Ronghui; Li, Yanfeng; Liu, Yuanhong; Hu, Yunsheng
Abstract : Phosphor Ca2 LuZrScAl2 GeO12 :Ce is synthesized. Crystal structure, electronic structure and luminescence property of samples are investigated. Electronic structure study indicates that photo-ionization easy occur when the matrix contains Ge 4+ or Zr 4+ . Abstract : A series of new garnet phosphors, Ca2 Lu1− x ZrScAl2 GeO12 : x Ce 3+ (0.005 ≤ x ≤ 0.1), have been successfully synthesized through a conventional high-temperature solid-state reaction method. The crystal structure and electronic structure of the host, and the morphology, luminescence property, diffuse reflectance spectra, fluorescence lifetime and thermal stability of the phosphors are investigated in this article. The crystal structure was characterized by X-ray diffraction Rietveld refinement and it belongs to the Ia 3̄ d (230) space-group. The band gap of this matrix is about 5.15 eV, which is much narrower than that of YAG, enhancing the possibility of photo-ionization. The optimized phosphor can be excited by UV or near-UV light in the range of 320–420 nm and exhibits a broad blue-green emission centering at 472 nm under 405 nm excitation. In addition, the concentration quenching mechanism and differentiation of dodecahedral sites were discussed in detail.